Brand Experience Terhadap Repurchase Intention Kosmetik Halal pada Masyarakat Muslim di Kota Singkawang - Aya Sofia Ardelia (ITB AAS INDONESIA Surakarta, 2025)
Consumer behavior in general is described as a form of process from searching, selecting to the stage of deciding to buy a product or service in order to provide for their needs. Brand Experience is the sensation, feeling, cognition and response or consumer response to the brand. In Islam, a Muslim in the practice of buying and selling must pay attention to whether the goods sold are halal and free from usury elements, both sellers and consumers and must be based on mutual consent or mutual need. The goods sold do not contain elements of fraud and consumers know the quality and specifications of the product clearly. If these things are met, of course consumers can get a positive experience from the products they buy such as satisfaction, feelings of pleasure or happiness when buying and wanting to buy again so that they can create a Brand Experience or experience felt by consumers towards the brands they consume. Therefore, researchers are interested in conducting research to determine the effect of Branding Experience on Repurchase Intention of halal cosmetics in the community in Singkawang. This research is a quantitative field research by distributing questionnaires and analyzed using a simple linear regression analysis method using the SPSS test tool. The test results prove that Branding Experience on Repurchase Intention of halal cosmetics in the community in Singkawang.